Academic Senate Minutes 2006-05-25 - Academic Senate:::::::::
Agenda amended and approved. Minutes of 5/11/06 approved. Degree name change for CCJ approved. Candidates for Graduation approved. Information item from EPC on Program Reviews. Chair's Report. Faculty Consultation in Budgetary Matters approved. APC: Changing Schools to Colleges tabled. President Report. Vice President of Associated Students Report. Statewide Senator report. APC report. Resolution Regarding Contracting Bookstore Services to Barnes and Noble approved. Changing of the Guard.